Coastal Community Behavior Patterns Related to Hypertension Treatment: A Case Study - Dian Ayu Irhamna; Fahmi Ichwansyah; Meutia Zahara (Indonesian Journal of Global Health Research, 2025)
Hypertension is a high-risk non-communicable disease and is known as a "silent killer" because it often does not show clear symptoms. Coastal communities in Pidie Jaya Regency face various challenges in accessing health services, including economic, cultural, and geographical limitations, which affect their behavioral patterns in seeking treatment. This study aims to understand the behavioral patterns of coastal communities in accessing health services for hypertension treatment and the factors that influence it. This study uses a qualitative approach with descriptive analysis based on case studies. Data were obtained through in-depth interviews with 27 informants, consisting of hypertension sufferers, families, health workers, and village heads in five coastal sub-districts of Pidie Jaya Regency. The majority of people are more familiar with the term "high blood pressure" than "hypertension" and tend to choose traditional medicine over medical treatment. Awareness of routine check-ups is still low, and access to health facilities is influenced by economic factors and transportation limitations. Culture-based health education, increasing access to health services, and improving drug distribution systems are needed to increase awareness and compliance of coastal communities in managing hypertension.